A walk through the southern sky : a guide to stars, constellations and their legends - Heifetz, Milton D., 1921-2015 (Cambridge University Press, 2012)
A Walk through the Southern Sky is a beautifully illustrated guide to the stars and constellations of the southern hemisphere. By following the simplified and easy-to-use starmaps, readers will be able to identify constellations with no equipment but normal sight and a clear night sky.